2015
DOI: 10.1039/c5ra11464k
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of g-C3N4/WO3 heterojunction plates array films with enhanced photoelectrochemical performance

Abstract: heterojunction plate array films with enhanced photoelectrochemical (PEC) performance were successfully synthesized through a combination of hydrothermal and dipping-annealing methods.Urea aqueous solutions were prepared as the precursors to in situ synthesize g-C 3 N 4 nanoparticles on the surface of WO 3 platelets. The PEC performances of the photoanodes were investigated by the photocurrent density and incident photon-to-current conversion efficiency (IPCE). As-prepared g-C 3 N 4 /WO 3 heterojunction films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 70 publications
(106 reference statements)
0
31
0
Order By: Relevance
“…All the diffraction peaks observed in XRD patterns of S-0, S-1, S-2, S-3, and S-4 could be indexed to the standard data of WO 3 (JCPDS 43-1035). The diffraction peaks of g-C 3 N 4 could not be found because of the low concentration of g-C 3 N 4 in the composites [14]. It was reported that the diffraction peaks of g-C 3 N 4 did not appear in the XRD patterns of g-C 3 N 4 -WO 3 composites when the content of WO 3 was higher than 10 wt% [15].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…All the diffraction peaks observed in XRD patterns of S-0, S-1, S-2, S-3, and S-4 could be indexed to the standard data of WO 3 (JCPDS 43-1035). The diffraction peaks of g-C 3 N 4 could not be found because of the low concentration of g-C 3 N 4 in the composites [14]. It was reported that the diffraction peaks of g-C 3 N 4 did not appear in the XRD patterns of g-C 3 N 4 -WO 3 composites when the content of WO 3 was higher than 10 wt% [15].…”
Section: Resultsmentioning
confidence: 95%
“…Figure 1 shows the XRD patterns of pure g-C 3 N 4 , g-C 3 N 4 -WO 3 (S-1, S-2, S-3, and S-4), and WO 3 . Two significant diffraction peaks were observed at 13.23°and 27.86°in the XRD pattern of g-C 3 N 4 , indicating the (100) and (002) planes of layered g-C 3 N 4 ; the weaker peak at 13.23°indicates the in-planar tris-s-triazine structural packing, and the stronger peak at 27.86°corresponds to the stacked of the aromatic systems between layers [6][7][8]14]. All the diffraction peaks observed in XRD patterns of S-0, S-1, S-2, S-3, and S-4 could be indexed to the standard data of WO 3 (JCPDS 43-1035).…”
Section: Resultsmentioning
confidence: 99%
“…RHE) by extrapolating the X‐intercepts of the M−S plots. This negative shift evidences a more efficient charge transfer and better separation of photo‐generated carriers . The bottom of conduction band (CB) can be estimated by V FB since it is more negative by 0.1∼0.3 V than V FB .…”
Section: Resultsmentioning
confidence: 99%
“…(G) LSV curves of WO 3 /g‐C 3 N 4 NSA photoanodes with different g‐C 3 N 4 content. (Reproduced with permission: Copyright 2015, the Royal Society of Chemistry 123 …”
Section: Small Bandgap Metal Oxide/g‐c3n4 Heteroarrays As Photoanodesmentioning
confidence: 99%